2010
DOI: 10.1111/j.1600-0560.2009.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous porokeratosis of the gluteal cleft (porokeratosis ptychotropica): a rare disorder easily misdiagnosed

Abstract: Porokeratosis represents a heterogeneous group of disorders characterized clinically by a distinctive ridge-like border and histologically by cornoid lamellae. A verrucous variant of porokeratosis involving the gluteal cleft has been recently described. We present 5 new cases and review the current literature to highlight the clinical and histopathologic features of this disorder. Descriptive terms including hyperkeratotic porokeratosis, genitogluteal porokeratosis, porokeratoma, follicular porokeratosis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
84
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 24 publications
2
84
0
2
Order By: Relevance
“…There have been no associations of this disease with immune suppression thus far. A recent case series and literature review suggests a possible autosomal dominant pattern of inheritance from a series of patients from the same family line 3 . The same review also found a predilection of the disease for males, reporting that 21 of the 23 published cases referred to men 3 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There have been no associations of this disease with immune suppression thus far. A recent case series and literature review suggests a possible autosomal dominant pattern of inheritance from a series of patients from the same family line 3 . The same review also found a predilection of the disease for males, reporting that 21 of the 23 published cases referred to men 3 .…”
Section: Discussionmentioning
confidence: 94%
“…A recent case series and literature review suggests a possible autosomal dominant pattern of inheritance from a series of patients from the same family line 3 . The same review also found a predilection of the disease for males, reporting that 21 of the 23 published cases referred to men 3 . Although no skin malignancies have yet been reported with this variant, it is important to understand that all five primary clinical variants of porokeratosis have been associated with squamous cell carcinoma, and basal cell carcinoma or melanoma 4 …”
Section: Discussionmentioning
confidence: 99%
“…Verrucous porokeratosis has been proposed to unify all these terms. [4] Clinically, these cases of verrucous porokeratosis frequently show psoriatic-like plaques in butterfly-shape on the buttocks surrounding the anus and occasional satellite lesions. [45] Histopathologically, there are multiple concentric cornoid lamellae over a digitate epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Clinically, these cases of verrucous porokeratosis frequently show psoriatic-like plaques in butterfly-shape on the buttocks surrounding the anus and occasional satellite lesions. [45] Histopathologically, there are multiple concentric cornoid lamellae over a digitate epidermis. [46] Although both entities share the presence of multiple cornoid lamellae, lesions of porokeratoma clinically and histologically differ from verrucous (hyperkeratotic) porokeratosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation